2017
DOI: 10.1002/cne.24318
|View full text |Cite
|
Sign up to set email alerts
|

The physiological motor patterns produced by neurons in the nucleus retroambiguus in the rat and their modulation by vagal, peripheral chemosensory, and nociceptive stimulation

Abstract: The nucleus retroambiguus (NRA) is a neuronal cell group in the medullary ventrolateral tegmentum, rostrocaudally between the obex and the first cervical spinal segment. NRA neurons are premotor interneurons with direct projections to the motoneurons of soft palate, pharynx, and larynx in the nucleus ambiguus in the lateral medulla as well as to the motoneurons in the spinal cord innervating diaphragm, abdominal, and pelvic floor muscles and the lumbosacral motoneurons generating sexual posture. These NRA prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Local stimulation of PAG subdivisions evokes several respiratory responses including the recruitment of abdominal expiratory activity and vocalization (Farmer, Bautista, Jones, Stanic, & Dutschmann, 2014;Huang, Subramanian, Balnave, Turman, & Moi Chow, 2000;Subramanian, 2013;Subramanian, Balnave, & Holstege, 2008;Zhang et al, 2005). It has been suggested that these effects are mediated indirectly via the parabrachial and KF nuclei (Dutschmann & Dick, 2012) or expiratory premotoneurons in the cVRG (Jones, Saad, Lewis, Subramanian, & Dutschmann, 2012;Subramanian, Huang, Silburn, Balnave, & Holstege, 2018), but the direct, primarily excitatory projection that we have described here from various PAG subdivisions to the pF L may also be involved in this process.…”
Section: Pag Regionmentioning
confidence: 53%
“…Local stimulation of PAG subdivisions evokes several respiratory responses including the recruitment of abdominal expiratory activity and vocalization (Farmer, Bautista, Jones, Stanic, & Dutschmann, 2014;Huang, Subramanian, Balnave, Turman, & Moi Chow, 2000;Subramanian, 2013;Subramanian, Balnave, & Holstege, 2008;Zhang et al, 2005). It has been suggested that these effects are mediated indirectly via the parabrachial and KF nuclei (Dutschmann & Dick, 2012) or expiratory premotoneurons in the cVRG (Jones, Saad, Lewis, Subramanian, & Dutschmann, 2012;Subramanian, Huang, Silburn, Balnave, & Holstege, 2018), but the direct, primarily excitatory projection that we have described here from various PAG subdivisions to the pF L may also be involved in this process.…”
Section: Pag Regionmentioning
confidence: 53%
“…Even though the latter study carefully disentangles a PAG to hindbrain vocal circuit in the context of mate choice, showing that female affiliative behaviors towards the male are clearly reduced when male calling is prevented, it is still unknown how male USVs shape female preference at the neural circuit level. In general, studies in female rats (Sakuma and Pfaff, 1979 ; Yamada and Kawata, 2014 ) and mice (Ishii et al, 2017 ) point to a lordosis modulating role of the PAG supported by anatomical studies that have uncovered various PAG-brainstem projections that are activated during mating (Yamada and Kawata, 2014 ; Subramanian et al, 2018 ; Lo et al, 2019 ).…”
Section: Neural Circuits For Auditory and Somatosensation In The Cont...mentioning
confidence: 99%
“…We also found very strong connectivity with the thalamus, hypothalamus, pallidum, amygdala, and the cerebellar cortex. The retroambiguus nucleus is a multifunctional group of neurons involved in the output of the emotional motor system, such as vomiting, vocalization, mating, and changes in respiration (Subramanian, Huang, Silburn, Balnave, & Holstege, 2018 ). The periaqueductal gray (PAG)–nucleus retroambiguus (NRA) pathway has been shown to be involved in control of vocalization and sexual behavior and is evident by iMRt connectivity to PAG and amygdala here.…”
Section: Discussionmentioning
confidence: 99%